1985
DOI: 10.3109/00498258509045346
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent elimination of theophylline in rats

Abstract: The effect of different doses on the rate of metabolism of theophylline in rats was investigated. After doses of 52 or 115 mg/kg, the initial concn. decayed according to a first-order process with an apparent half-life of about four hours. However, after four to eight hours the slope of the curves declined, resulting in elimination half-lives of about 70 min. Similar half-lives of 70 min were also found after doses of 6 or 11 mg/kg. The AUC increased disproportionately with dose, indicating capacity-limited el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…Recent studies on the metabolic inhibition of enoxacin in rats, however, suggested that quinolones may affect the pathway of theophylline metabolism for oxidation in addition to affecting N demethylation (6,20). Further detailed studies concerning whether quinolones selectively act in the metabolic pathway of theophylline in humans are necessary, although the pathways of theophylline metabolism in humans and rats are considered to be quite similar (3,27).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on the metabolic inhibition of enoxacin in rats, however, suggested that quinolones may affect the pathway of theophylline metabolism for oxidation in addition to affecting N demethylation (6,20). Further detailed studies concerning whether quinolones selectively act in the metabolic pathway of theophylline in humans are necessary, although the pathways of theophylline metabolism in humans and rats are considered to be quite similar (3,27).…”
Section: Discussionmentioning
confidence: 99%
“…Many investigators have reported the dose-dependent metabolic disposition of theophylline in humans [19][20][21][22] and in rats [23]. Therefore, in the present study, we used both a single low dose of 5 mg/kg of theophylline and multiple high doses of 50 mg/kg of the drug twice daily for 3 days, which has been reported to indicate linear and nonlinear pharmacokinetics, respectively [23], and investigated the ef fect of combination of ofloxacin, enox acin and cimetidine on the pharmacoki netics of theophylline.…”
Section: Discussionmentioning
confidence: 99%
“…Many investigators reported dose-dependent metabolic disposition of theophylline in humans (Lesko, 1979;Massey et al, 1984) and rats (Teunissen et al, 1985). Thus, theophylline at a dose of 5 mg/kg, which has been reported to be in the ranges of dose-independent metabolic disposition of theophylline in rats (for up to 10 mg/kg) (Teunissen et al, 1985), was administered intravenously or orally to rats.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, theophylline at a dose of 5 mg/kg, which has been reported to be in the ranges of dose-independent metabolic disposition of theophylline in rats (for up to 10 mg/kg) (Teunissen et al, 1985), was administered intravenously or orally to rats. The expression of hepatic CYP1A subfamily, 2B1/2, and 3A subfamily in three groups of rats is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%